Eficiência da terapia fotodinâmica em Staphylococcus aureus e Escherichia coli - Ronqui, Maria Rita [UNESP] (2015)
The occurrence of a variety of pathogens resistant to current antibiotics remains the major problem especially when bacterial infections are growing in biofilm. In this study, we propose the use of photodynamic therapy (PDT) as monotherapy and also associated with antibiotic therapy as an alternative treatment. The aim of this study was to analyze the effects of PDT mediated by methylene blue (MB) on Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) as biofilm and planktonic phase. Different concentrations of photosensitizer (400; 200; 100; 50; 25; 12,5; 6,25g/mL), and fluency of 2.8; 5.6; 11.2 22,4J/cm2 were tested. We also carried out experiments that evaluated the synergistic effect of photodynamic therapy and antibiotic ciprofloxacin. The bactericidal effects with PDT as monotherapy were not statistically increased with the concentration of photosensitizer and bacteria in biofilms were less than affect in the planktonic phase. Although, the synergistic effect of photodynamic therapy on biofilms followed by ciprofloxacin amplified the bacterial reduction. In biofilm for S. aureus, using 50 μg/ml MB, irradiation 22,4 J/cm² and the concentration of 15,625 μg/mL of antibiotic, got a reduction of 61,80%. For E. coli, there was a bacterial eradication at all concentrations tested in PDT combined with antibiotic, both the irradiation 11,2 J/cm² as the irradiation 22,4 J/cm². Bacterial growth was observed only in the lowest tested concentration of the antibiotic, 0,125 μg/mL, at concentrations of 50 and 25 μg/mL MB.